PENGUKURAN KINERJA VOIP DENGAN CODEC G.711?, G.711a DAN G.729 DI MEDIA TRANSMISI NIRKABEL BERBASIS SIP DAN IAX - Susiani Pande, Putu Sintia; Sudiarta, Pande Ketut; Oka Widyantara, I Made (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUM, 2018)
Voice over Internet Protocol (VoIP) is a technology that can send real-time data with IP-based networks (Internet Protocol). In VoIP technology with wireless network has several problems that cause the performance of the network to be varied due to the QoS (Quality of Service) include delay, jitter, packet loss and MOS that affect the wireless network. This research uses G.711?, G.711a and G.729 codec based on SIP and IAX server on wireless network which then the QoS result from each codec compared with ITU-T standard which become the reference of whether the network is good or not so that later can realized on campus. In the research results, QoS on wireless IEEE 802.11 b has linear results, whereas QoS wireless in VoIP has fluctuating results because the use of codecs in VoIP on each codec has a large bitrate and different coding techniques and is a feature of wireless networks. The QoS comparison of three codecs produced the best G711 Q7S codecs because the G.711 codec has a bitrate that conforms to the 64 kbps voice communication standard and uses voice coding techniques that match the digital signal encoding technique of PCM (Pulse Code Modulation).